2012
DOI: 10.2478/s11536-012-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Relation between bone density and certain parameters of lipid status in postmenopausal women

Abstract: AbstractThe aim of the paper was to examine the relation between bone density and certain parameters of lipid status in postmenopausal women. The research involved 300 women referred to densitometric examination as they belonged to the risk group of postmenopausal women. All the examinees had the following biochemical parameters determined: total cholesterol, triglycerides, HDL cholesterol, LDL cholesterol, glycemia, serum Ca and P. Univariate logistic regression analyses showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…Not all anatomic sites had the same association factors, but their positive or negative correlation was consistent. The parameters and association tendencies were also similar to the ones described in the literature [ 7 8 9 10 11 12 13 14 15 ].…”
Section: R Esultssupporting
confidence: 80%
See 1 more Smart Citation
“…Not all anatomic sites had the same association factors, but their positive or negative correlation was consistent. The parameters and association tendencies were also similar to the ones described in the literature [ 7 8 9 10 11 12 13 14 15 ].…”
Section: R Esultssupporting
confidence: 80%
“…Hyperlipidemia increases the risk for generating lipid oxidation products, which accumulate in the subendothelial spaces of the vasculature and bone, impairing bone regeneration and its mechanical strength; thus, these oxidation products may be risk factors for osteoporosis [ 14 32 ]. There is an inverse relationship between lumbar spine and whole-body BMD and serum TCH and LDL-C levels in postmenopausal women and HDL-C in premenopausal women [ 15 33 ]. Serum lipids, especially low HDL-C and high LDL-C, influence BMD by acting on the long bones and affecting osteoporosis and osteopenia [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al found that high-density lipoprotein cholesterol (HDL-C) levels in serum are positively associated with trochanteric BMD; however, HDL-C levels were significantly lower in the control group than in the group with fractures [13]. Similar results were reported by Dimic et al [15]. On the other hand, other studies demonstrated that HDL-C level was significantly higher in osteoporotic patients than in controls, and the risk of osteoporosis was significantly higher in women with a higher level of HDL-C [16,17].…”
Section: Introductionsupporting
confidence: 63%
“…On the other hand, other studies demonstrated that HDL-C level was significantly higher in osteoporotic patients than in controls, and the risk of osteoporosis was significantly higher in women with a higher level of HDL-C [16,17]. Associations of BMD with serum triglycerides have been found to be positive [18], negative [15], and neutral [19].…”
Section: Introductionmentioning
confidence: 95%
“…Animal models support the association between osteoporosis and atherosclerosis (Parhami et al, 2000 ; Price et al, 2001 ). Observational studies have shown that higher atherogenic lipid profile and lipoproteins are inversely associated with bone density (Dimic et al, 2012 ; Sarkis et al, 2012 ) but the exact mechanisms underlying this relationship are unclear (Farhat and Cauley, 2008 ).…”
Section: Introductionmentioning
confidence: 99%